Information technology and its impact on the creative behavior of employees: a field study in the scientific and administrative units at the University of Karbala - حسين حريجة غالي (Iraqi Journal for Administrative Sciences, 2024)
The Study aims to Determined Relationship and Impact of Information Technology (Computer , Programmers , Data Bases , Communication , Internet ) in Innovational Behavior for Employees in Units Managerial and Scientific in Karbala University , In Order to Achieve The Aims of The Study , It is Divided to (5) Chapter , The First for Study Methodology , The Second Contains Theoretical Review for Study Variables , The Third Represent Description and Diagnosis Study Variables , The Forth Show The Data Analysis and Discuss The ApplicantResults , While The Fifth Refers to Some Conclusion and Recommendation The Study Sampling (88) Employees in The Concerning Departments , Results Refer That The Hypothesis of Research has Achieved Necessity to Assume Managers of Managerial and Scientific Units Largest Interest for Impact and Relationship Information Technology in Innovation Behavior for Employees .